Christiana's journey : a Victorian children's story based on John Bunyan's Pilgrim's progress, part 2. - Wright, Christopher; Taylor, Helen L. (Helen Louisa); Bunyan, John, 1628-1688. (South Plainfield, N.J. : Bridge Pub., 1982)
Christiana sets out on a perilous journey with her three brothers and her little sister Innocence, hoping to join their parents and the pilgrim Christian in the Heavenly City.
Adaptation by C. Wright of: Christiana / Helen L. Taylor, which was an adaptation of pt. 2 of: Pilgrim's progress / John Bunyan.
Keywords: Pilgrims and pilgrimages -- Fiction